Powered by www.myengg.

com

DEFINITE INTEGRATION
PREVIOUS EAMCET BITS
π

1.

1

∫ 1 + sin x dx =

[EAMCET 2009]

0

1) 1

2) 2

3) – 1

4) – 2

Ans: 2
π

Sol:

1

1 − sin x

∫ 1 + sin x × 1 − sin x dx
0

π

π

1 − sin x
=∫
dx ⇒ ∫ ( sec2 x − sec x tan x ) dx
2
cos
x
0
0
= ( tan x − sex )0

π

= [ tan π − sec π] − [ tan 0° − sec 0°]
= ( 0 + 1) − ( 0 − 1) = 2
1

2.

∫x

3/ 2

1 − xdx =

[EAMCET 2008]

0

1)

π
6

2)

π
9

3)

π
12

4)

π
16

Ans: 4
Sol: Put x = sin 2 θ then dx = 2sin θ cos θdθ
Also x = 0, 1 ⇒ 0, π/2
1

3/ 2
∫ x 1 − xdx =

π/ 2

0

∫ sin

3

θ 1 − sin 2 θ.2sin θ cos θdθ

0

π/2

1 3 1 π π
= 2 ∫ sin 4 θ co s 2 θdθ = 2 × × × × =
6 4 2 2 16
0
π/ 2

3.

sin x dx =

[EAMCET 2008]

−π / 2

1) 0

2) 1

3) 2

Ans:3
π/ 2

Sol:

−π / 2

0

sin x dx =

sin ( − x ) dx +

−π / 2

π/2

∫ sin xdx
0

= [ cos x ]−π / 2 + [ − cos x ]0

π/ 2

0

= 1− 0 − 0 +1 = 2

Powered by www.myengg.com

4) π

Powered by www.myengg.com

Definite Integration

4.

t

If f ( x ) =

e

−x

2

−t

dx then Lt f ( t ) is

[EAMCET 2007]

t →∞

1) 1

2) 1/2

3) 0

4) – 1

Ans:1
ex
e− x
dx
+
∫2
∫0 2 dx
−t
0

Sol: f ( t ) =

t

=

t
1 x 0 1
⎡⎣e ⎤⎦ + ⎡⎣ −e − x ⎤⎦
−t
0
2
2

=

1
1
1 1
1
1
⎡⎣1 − e − t ⎤⎦ − ⎡⎣e − t − 1⎤⎦ = − e − t − e − t +
2
2
2 2
2
2

= 1 − e− t

f(t)

Lt f (t) = Lt ⎡⎣1 − e − t ⎤⎦ = 1 − e−∞ = 1 − 0 = 1
t →∞
x →∞

5.

∫ sin

x cos5 xdx =

6

[EAMCET 2007]

0

1) 2π

2)

π
2

3) 0

4) – π

Ans: 3

Sol: I =

∫ sin

6

x cos5 xdx

0

Let f (x) = sin 6 x cos5 x
f ( 2π − x ) = f ( x )
π

I = 2∫ sin 6 x cos5 xdx
0

f ( π − x ) = sin 6 ( π − x ) cos5 ( π − x )
= − sin 6 x cos5 x = −f (x)
∴I = 0
π/ 2

6.

dx

∫ 1 + tan

3

0

x

=

[EAMCET 2006]

1) π

2)

π
2

3)

π
4

Ans: 3
π/ 2

Sol: Let I =

dx

∫ 1 + tan
0

3

x

Powered by www.myengg.com

4)


2

Powered by www.myengg.com

Definite Integration
π/ 2

=

0

π/ 2

=

0

π/ 2

=

0

cos3 x
dx ……….(1)
sin 3 x + cos3 x

⎛π

cos3 ⎜ − x ⎟
2


dx
π



3
3⎛π
sin ⎜ − x ⎟ + cos ⎜ − x ⎟
⎝2

⎝2

sin 3 x
dx …………(2)
cos3 x + sin 3 x

(1) + (2)
π/ 2

∫ 1.dx

2I =

0

2I =
1

7.

π
π
⇒I=
2
4

cosh x

∫ 1+ e

2x

dx =

[EAMCET 2006]

−1

1) 0

2) 1

3)

e2 − 1
2e

4)

e2 + 2
2e

Ans: 3

ex + e− x
dx

2x
−1 2 (1 + e )
1

Sol:


ex + e− x ⎤
=

cosh
x

2 ⎥⎦

e 2x + 1
1 −x
∫−1 2ex (1 + e2x ) dx ⇒ 2 −∫1 e dx
1

=

1

1

1
1
1
= ∫ e− x dx ⇒ ⎡⎣ −e − x ⎤⎦
−1
2 −1
2

1
e2 − 1
= − ⎡⎣e −1 − e1 ⎤⎦ ⇒
2
2e
π/ 2

8.


0

200sin x + 100 cos x
dx =
sin x + cos x

1) 50π

2) 25π

[EAMCET 2005]
3) 75π

Ans: 3
π/ 2

Sol:


0

π/ 2


0

a sin x + b cos x
π
dx = ( a + b )
sin x + cox
4
200sin x + 100 cos x
π
dx = ( 200 + 100 ) = 75π
sin x + cos x
4

Powered by www.myengg.com

4) 150π

Powered by www.myengg.com

Definite Integration
π

9.

θ sin θ

∫ 1 + cos

2

0

θ

dθ =

[EAMCET 2005]

π2
2

1)

2)

π3
3

3) π2

4)

π2
4

Ans: 4
π

Sol: Let I =

θ sin θ

∫ 1 + cos

2

0

θ

( π − θ ) sin ( π − θ ) dθ ⇒ π ( π − θ ) sin θ dθ
∫0 1 + cos2 ( π − θ )
∫0 1 + cos2 θ
π

=

π

π/ 2

sin θ
sin θ
I = π∫
dθ − I = 2I = π.2 ∫
dθ let cosθ = 5 , - sinθdθ = dt
2
1 + cos θ
1 + cos 2 θ
0
0
−dt
1
I = π∫
⇒ π∫
dt
2
1+ t
1+ t2
1
0
0

1

1
π2
⎡π ⎤
= π ⎡⎣ tan −1 t ⎤⎦ ⇒ I = π ⎢ − 0 ⎥ ⇒ I =
0
4
⎣4

π/ 2

10.

⎛ 2 − sin θ ⎞
log ⎜
⎟ dθ =
⎝ 2 + sin θ ⎠
−π / 2

1) 0

[EAMCET 2004]

2) 1

3) 2

4) – 1

Ans: 1

⎛ 2 − sin θ ⎞
Sol: Let f (θ) = log ⎜

⎝ 2 + sin θ ⎠
⎛ 2 + sin θ ⎞
⎛ 2 − sin θ ⎞
f (−θ) = log ⎜
⎟ = − log ⎜

⎝ 2 − sin θ ⎠
⎝ 2 + sin θ ⎠
f ( −θ ) = −f ( θ )
∴ It is an odd function
π/2

∴I =
2

11.

⎛ 2 − sin θ ⎞
log ⎜
⎟ dθ = 0
⎝ 2 + sin θ ⎠
−π / 2

2x − 2

∫ 2x − x

2

dx =

[EAMCET 2004]

0

1) 0

2) 2

3) 3

Ans: 1
2

Sol: Let I =

2x − 2

∫ 2x − x

2

dx

0

Powered by www.myengg.com

4) 4

Powered by www.myengg.com

Definite Integration
Put 2x − x 2 = t ⇒ ( 2 − 2x ) dx = dt
0

dt
=0
t
0

−∫
2

12.

∫ [ x ] dx =

[EAMCET 2003]

−2

1) 1

2) 2

3) 3

4) 4

Ans: 4
Sol:

−1

0

1

2

−2

−1

0

1

∫ [ x ] dx + ∫ [ x ] dx + ∫ [ x ] dx + ∫ [ x ] dx

=2+1+0+1=4
13.

1

0

∫ sin ⎜⎜ 2 tan
1)

1+ x ⎞
⎟dx =
1 − x ⎟⎠

−1

π
6

2)

[EAMCET 2003]

π
4

3)

π
2

4) π

Ans: 2
L.L : 0 = cosθ ⇒ θ = π / 2
U.L : 1 = cosθ ⇒ θ = 0°

Sol: Put x = cosθ
dx = - sinθdθ

=

0

π/ 2

∫ sin ⎢2 tan

π/ 2

=

−1

1 + cos θ ⎤
⎥ ( − sin θ )dθ
1 − cos θ ⎦

sin ( π − θ ) sin θdθ =

0

=
3

14.

π/ 2

∫ sin

2

θdθ

0

1 π π
× =
2 2 4
3x + 1
dx =
2
+9

∫x
0

(

[EAMCET 2003]

)

1) Log 2 2 +

π
π
2) Log 2 2 +
12
2

(

)

(

)

3) Log 2 2 +

π
6

Ans: 1
3

Sol: =

3

3 2x
1
dx + ∫ 2
dx
2

2 0 x +9
x +9
0
3

3
3
1⎡
x⎤
= ⎡⎣ Log ( x 2 + 9 ) ⎤⎦ + ⎢ tan −1 ⎥
0
2
3⎣
3 ⎦0

=

3
1
[ Log18 − Log9] + ⎡⎣ tan −1 (1) − tan −1 ( 0 )⎤⎦
2
3

Powered by www.myengg.com

(

)

4) Log 2 2 +

π
3

Powered by www.myengg.com

Definite Integration
3
π
π
Log2 + = Log23/ 2 +
2
12
12

=

(

)

= Log 2 2 +
3

15.

∫x

π
12

dx
=
−x

[EAMCET 2002]

2

2

1) log

2
3

2) log

4
3

3) log

8
3

4) log

1
4

Ans: 2
3

Sol:

dx
∫2 x 2 − x =

3

dx

∫ x ( x − 1)
2

3

1⎞
⎡ ⎛ x − 1 ⎞⎤
⎛ 1
= ∫⎜
− ⎟ dx = ⎢log ⎜
⎟⎥
x −1 x ⎠
⎣ ⎝ x ⎠⎦ x =2
2⎝
3

2
1
4
= log − log = log
3
2
3
π/ 2

16.

sin 4 x cos 6 xdx =

[EAMCET 2002]

−π / 2


128

1)

2)


256

3)


572

4)


64

Ans: 2
π/ 2

Sol:

π/2

−π / 2

sin 4 x cos 6 xdx = 2 ∫ sin 4 x cos 6 xdx
0

⎡ 3 1 5 3 1 π ⎤ 3π
= 2⎢ . . . . . ⎥ =
⎣10 8 6 4 2 2 ⎦ 256
π/ 2

17.

∫ sin

x cos 2 xdx =

8

[EAMCET 2001]

0

π
512

1)

2)


512

3)


512

4)


512

Ans: 4
π/ 2

Sol:

∫ sin

8

x cos 2 xdx

0

=

7 5 3 1 1 π 7π
. . . . . =
10 8 6 4 2 2 512

1

18.

∫ ( ax

3

+ bx ) dx = 0 for ;

[EAMCET 2001]

−1

Powered by www.myengg.com

Powered by www.myengg.com

Definite Integration

1) any values of a and b

2) a > 0 and b > 0 only

3) a > 0 and b < 0 only

4) a < 0 and b < 0 only

Ans: 1
Sol: ax 3 + bx is odd function
1

∫ ( ax

3

+ bx ) dx = 0

−1

for any values of ‘a’ and ‘b’
19.

⎛ 10 −2n
⎞ ⎛ 10 2n +1 27

27
⎜ ∑ ∫ sin xdx ⎟ + ⎜ ∑ ∫ sin xdx ⎟
⎝ n =1 2n −1
⎠ ⎝ n =1 2n

1) 27 2

[EAMCET 2000]

2) – 54

3) 54

4) 0

Ans: 4
Sol: sin27x is odd function
1

20.

x

∫ (1 − x )

5/ 4

dx =

[EAMCET 2000]

0

16
3

1)

3
16

2)

3)

−3
16

4)

−16
3

Ans: 4
1

Sol:

∫ (1 − x )

1− x

1

x

5/ 4

dx =

0

∫ ⎡(1 − 1 − x )
0

1− x
dx
x 5/ 4
0

1

5/ 4


dx ⇒ ∫

−16
1 ⎞
⎛ 1
= ∫ ⎜ 5/ 4 − 1/ 4 ⎟ dx =
x
x ⎠
3
0⎝
1

a

21.

If f(x) is integrable on [0, a] then

f (x)

∫ f ( x ) + f ( a − x ) dx =

[EAMCET 2000]

0

1) 0

2) 1

3) a

Ans: 4
f (x)

a

Sol: I =

∫ f ( x ) + f ( a − x ) dx ………………(1)
0

f (a − x )

a

⇒I=∫
0

f (a − x ) + f ( x )

dx …………..(2)

(1) + (2)
a

⇒ 2I = ∫ I dx ⇒ I =
0

a
2

Powered by www.myengg.com

4) a/2

Powered by www.myengg.com

Definite Integration

22.

1
1 ⎤
⎡ 1
lim ⎢
+
+ ..... +
n →∞ 2n + 1
2n + 2
2n + n ⎥⎦

⎛1⎞
1) log e ⎜ ⎟
⎝3⎠

⎛2⎞
2) log e ⎜ ⎟
⎝3⎠

[EAMCET 2000]

⎛3⎞
3) log e ⎜ ⎟
⎝2⎠

Ans: 3

1
1 ⎤
⎡ 1
Sol: lim ⎢
+
+ ..... +
n →∞ 2n + 1
2n + 2
2n + n ⎥⎦

n
⎛ 1 ⎞
= lim ∑ ⎜

n →∞
r =1 ⎝ 2n + r ⎠
n

= lim ∑
n →∞

r =1

1
r⎞

n⎜2+ ⎟
n⎠

1
dx
⎛3⎞
= ⎡⎣log ( 2 + x ) ⎤⎦ 0 = log e ⎜ ⎟
2+x
⎝2⎠
0

1

=∫

DDD

Powered by www.myengg.com

⎛4⎞
4) log e ⎜ ⎟
⎝3⎠